Family Literacy and Colonial Logics - Crooks, Stacey Rae (2017)
This thesis is located in my relationship to Treaty 4 land, the traditional land of the Cree, Saulteaux, Lakota, Nakota, Dakota and Métis people. It starts with me, a 5th generation white settler, learning to see myself as a treaty person. Intertwined with this awareness is my developing understanding of the way that the “myth of the fort” and “colonial frontier logics” (Donald 2009b, 2009c, 2012a) shape educational practice in Saskatchewan. The focus of my research is family literacy programs, policy and research, and the assumption of deficit that I argue pervades this area of literacy education practice. As a community-based family literacy practitioner, working for many years mostly with New Canadians, I have wondered about a tension between the rhetorical commitment to strengths-based practice in the field and the ongoing presence/tenacity of deficit thinking in literacy practice. In exploring deficit thinking I have come to see how it is racialized and racializing (Valencia, 1997, 2010). As I explored in my study deficit thinking and race in family literacy work in Saskatchewan, I further came to recognize the significance of settler colonialism in shaping literacy practice. Eventually I understood, in a new way, that all family literacy programs in Saskatchewan take place on treaty land, and that the people in the programs, practitioners and families alike, are “all treaty people.” This analysis has been shaped by literature on race, whiteness and colonialism (Ahmed, 2007b; Donald, 2009c; Leonardo Porter, 2010). I have been informed by the ways in which feminist poststructuralists (Ahmed 2002, 2006, 2007a; Pillow, 2000, 2003, 2004, 2015; St. Pierre, 2000) talk about power, subjectivity and discourse. Feminist genealogical approaches (Pillow, 2003, 2004; Tamboukou 2003b; Tamboukou Ball, 2003) have directed me to explore the history of family literacy. The methods of Métissage (Hasebe-Ludt, Chambers, Leggo, 2009) and Indigenous Métissage (Donald, 2009b, 2012b) have informed how I have made sense of my research journey. Observing community programs in Aboriginal settings has led me to focus on how a robust understanding of respect might enable movement away from a racializing deficit thinking and towards ‘better’ relationships (Ahmed, 2002) or towards what Donald (2009c) calls “ethical relationality” in education practice and policy. Ph.D.